Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Genome-wide analyses provide insights into genetic variation, phylo- and co-phylogenetic relationships, and biogeography of the entomopathogenic nematode genus Heterorhabditis - Ricardo A.R. Machado; Arthur Muller; Alexandre Hiltmann; Aashaq Hussain Bhat; Vladimír Půža; Antoinette P. Malan; Carlos Castaneda-Alvarez; Ernesto San-Blas; Larry W. Duncan; David Shapiro-Ilan; Javad Karimi; Lalramliana; et al. (Molecular Phylogenetics and Evolution, 2025)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Reversal of high-fat diet-induced cognitive impairment and oxidative stress in the brain through Zingiber officinale supplementation - Thais Fernandes Luciano; Claudio Teodoro de Souza; Jade de Oliveira; Alexandre Pastoris Muller (Metabolic Brain Disease, 2024)

Right anterior insula ASL hypoperfusion as a diagnostic biomarker of prodromal and mild dementia with Lewy bodies: preliminary evidence using a Bayesian approach - Golda Gommel; Ludovic Jeanjean-Dormegny; Clément de Crespin de Billy; Olivier Mainberger; Augustin Moreau; Alexandre Obrecht; Rémi Vernet; Ilia Humbert; Benoit Schorr; Candice Muller; Catherine Demuynck; Paulo Loureiro de Sousa; et al. (GeroScience, 2024)

Serum Biomarkers to Mild Cognitive Deficits in Children and Adolescents - Lisiane Tuon; Natalia Santos Tramontin; Isis Custódio; Vitor Hugo Comim; Barbara Costa; Lariani Tamires Witt Tietbohl; Alexandre Pastoris Muller (Molecular Neurobiology, 2023)

Midpoint and endpoint characterization factors for mineral resource dissipation: methods and application to 6000 data sets - Alexandre Charpentier Poncelet; Philippe Loubet; Christoph Helbig; Antoine Beylot; Stéphanie Muller; Jacques Villeneuve; Bertrand Laratte; Andrea Thorenz; Axel Tuma; Guido Sonnemann (The International Journal of Life Cycle Assessment, 2022)
Purpose The accessibility to most metals is crucial to modern societies. In order to move towards more sustainable use of metals, it is relevant to reduce losses along their anthropogenic cycle. To this end, quantifying dissipative flows of mineral resources and assessing their impacts in life cycle assessment (LCA) has been a challenge brought up by various stakeholders in the LCA community. We address this challenge with the extension of previously developed impact assessment methods and evaluating how these updated methods compare to widely used impact assessment methods for mineral resource use. Methods Building on previous works, we extend the coverage of the average dissipation rate (ADR) and lost potential service time (LPST) methods to 61 metals. Midpoint characterization factors are computed using dynamic material flow analysis results, and endpoint characterization factors, by applying the market price of metals as a proxy for their value. We apply these methods to metal resource flows from 6000 market data sets along with the abiotic depletion potential and ReCiPe 2016 methods to anticipate how the assessment of dissipation using the newly developed methods might compare to the latter two widely used ones. Results and discussion The updated midpoint methods enable distinguishing between 61 metals based on their global dissipation patterns once they have been extracted from the ground. The endpoint methods further allow differentiating between the value of metals based on their annual average market prices. Metals with a high price that dissipate quickly have the highest endpoint characterization factors. The application study shows that metals with the largest resource flows are expected to have the most impacts with the midpoint ADR and LPST methods, metals that are relatively more expensive have a greater relative contribution to the endpoint assessment. Conclusion The extended ADR and LPST methods provide new information on the global dissipation patterns of 61 metals and on the associated potentially lost value for humans. The methods are readily applicable to resource flows in current life cycle inventories. This new information may be complementary to that provided by other impact assessment methods addressing different impact pathways when used in LCA studies. Additional research is needed to improve the characterization of the value of metals for society and to extend the methods to more resources.

Humoral immune response after COVID-19 infection or BNT162b2 vaccine among older adults: evolution over time and protective thresholds - Maxence Meyer; Florentin Constancias; Claudia Worth; Anita Meyer; Marion Muller; Alexandre Boussuge; Georges Kaltenbach; Elise Schmitt; Saïd Chayer; Aurélie Velay; Thomas Vogel; Samira Fafi-Kremer; et al. (GeroScience, 2022)

Life cycle impact assessment methods for estimating the impacts of dissipative flows of metals - Alexandre Charpentier Poncelet; Christoph Helbig; Philippe Loubet; Antoine Beylot; Stéphanie Muller; Jacques Villeneuve; Bertrand Laratte; Andrea Thorenz; Axel Tuma; Guido Sonnemann (Journal of Industrial Ecology, 2021)

Therapeutic prevention of COVID-19 in elderly: a case–control study - Frederic Blanc; Cedric Waechter; Thomas Vogel; Benoit Schorr; Catherine Demuynck; Catherine Martin Hunyadi; Maxence Meyer; Denata Mutelica; Nadjiba Bougaa; Samira Fafi-Kremer; Lidia Calabrese; Elise Schmitt; et al. (GeroScience, 2021)

Analysis of the Influence of Water Quality Parameters in the Final WQI Result Through Statistical Correlation Methods: Mirim Lagoon, RS, Brazil, Case Study - Marlon Heitor Kunst Valentini; Gabriel Borges dos Santos; Victória Huch Duarte; Henrique Sanchez Franz; Hugo Alexandre Soares Guedes; Rubia Flores Romani; Bruno Muller Vieira (Water, Air, & Soil Pollution, 2021)

Physical Exercise Training Improves Judgment and Problem-Solving and Modulates Serum Biomarkers in Patients with Alzheimer’s Disease - Joni Marcio de Farias; Natalia dos Santos Tramontin; Eduarda Valim Pereira; Geiziane Laurindo de Moraes; Beatriz Giusti Furtado; Lariani Tamires Witt Tietbohl; Bárbara Da Costa Pereira; Kellen Ugioni Simon; Alexandre Pastoris Muller (Molecular Neurobiology, 2021)

Musical Chairs on Temperate Reefs: Species Turnover and Replacement Within Functional Groups Explain Regional Diversity Variation in Assemblages Associated With Honeycomb Worms - Alexandre Muller; Camille Poitrimol; Flávia L. D. Nunes; Aurélien Boyé; Amelia Curd; Nicolas Desroy; Louise B. Firth; Laura Bush; Andrew J. Davies; Fernando P. Lima; Martin P. Marzloff; Claudia Meneghesso; et al. (Frontiers in Marine Science, 2021)
Reef-building species are recognized as having an important ecological role and as generally enhancing the diversity of benthic organisms in marine habitats. However, although these ecosystem engineers have a facilitating role for some species, they may exclude or compete with others. The honeycomb worm Sabellaria alveolata ( Linnaeus, 1767 ) is an important foundation species, commonly found from northwest Ireland to northern Mauritania, whose reef structures increase the physical complexity of the marine benthos, supporting high levels of biodiversity. Local patterns and regional differences in taxonomic and functional diversity were examined in honeycomb worm reefs from 10 sites along the northeastern Atlantic to explore variation in diversity across biogeographic regions and the potential effects of environmental drivers. While taxonomic composition varied across the study sites, levels of diversity remained relatively constant along the European coast. Assemblages showed high levels of species turnover compared to differences in richness, which varied primarily in response to sea surface temperatures and sediment content, the latter suggesting that local characteristics of the reef had a greater effect on community composition than the density of the engineering species. In contrast, the functional composition of assemblages was similar regardless of taxonomic composition or biogeography, with five functional groups being observed in all sites and only small differences in abundance in these groups being detected. Functional groups represented primarily filter-feeders and deposit-feeders, with the notable absence of herbivores, indicating that the reefs may act as biological filters for some species from the local pool of organisms. Redundancy was observed within functional groups that may indicate that honeycomb worm reefs can offer similar niche properties to its associated assemblages across varying environmental conditions. These results highlight the advantages of comparing taxonomic and functional metrics, which allow identification of a number of ecological processes that structure marine communities.

Gold Nanoparticles Treatment Reverses Brain Damage in Alzheimer’s Disease Model - Natalia dos Santos Tramontin; Sabrina da Silva; Rychard Arruda; Kellen Simon Ugioni; Paula Bortuluzzi Canteiro; Gustavo de Bem Silveira; Carolini Mendes; Paulo Cesar Lock Silveira; Alexandre Pastoris Muller (Molecular Neurobiology, 2020)

ATLANTIC EPIPHYTES : a data set of vascular and non‐vascular epiphyte plants and lichens from the Atlantic Forest - Flavio Nunes Ramos; Sara Ribeiro Mortara; Nathalia Monalisa‐Francisco; João Pedro Costa Elias; Luiz Menini Neto; Leandro Freitas; Rodrigo Kersten; André Márcio Amorim; Fernando Bittencourt Matos; André Felippe Nunes‐Freitas; Suzana Alcantara; Marcia Helena Nagahama Alexandre; et al. (Ecology, 2019)
Epiphytes are hyper‐diverse and one of the frequently undervalued life forms in plant surveys and biodiversity inventories. Epiphytes of the Atlantic Forest, one of the most endangered ecosystems in the world, have high endemism and radiated recently in the Pliocene. We aimed to (1) compile an extensive Atlantic Forest data set on vascular, non‐vascular plants (including hemiepiphytes), and lichen epiphyte species occurrence and abundance; (2) describe the epiphyte distribution in the Atlantic Forest, in order to indicate future sampling efforts. Our work presents the first epiphyte data set with information on abundance and occurrence of epiphyte phorophyte species. All data compiled here come from three main sources provided by the authors: published sources (comprising peer‐reviewed articles, books, and theses), unpublished data, and herbarium data. We compiled a data set composed of 2,095 species, from 89,270 holo/hemiepiphyte records, in the Atlantic Forest of Brazil, Argentina, Paraguay, and Uruguay, recorded from 1824 to early 2018. Most of the records were from qualitative data (occurrence only, 88%), well distributed throughout the Atlantic Forest. For quantitative records, the most common sampling method was individual trees (71%), followed by plot sampling (19%), and transect sampling (10%). Angiosperms (81%) were the most frequently registered group, and Bromeliaceae and Orchidaceae were the families with the greatest number of records (27,272 and 21,945, respectively). Ferns and Lycophytes presented fewer records than Angiosperms, and Polypodiaceae were the most recorded family, and more concentrated in the Southern and Southeastern regions. Data on non‐vascular plants and lichens were scarce, with a few disjunct records concentrated in the Northeastern region of the Atlantic Forest. For all non‐vascular plant records, Lejeuneaceae, a family of liverworts, was the most recorded family. We hope that our effort to organize scattered epiphyte data help advance the knowledge of epiphyte ecology, as well as our understanding of macroecological and biogeographical patterns in the Atlantic Forest. No copyright restrictions are associated with the data set. Please cite this Ecology Data Paper if the data are used in publication and teaching events.

Strength and Aerobic Exercises Improve Spatial Memory in Aging Rats Through Stimulating Distinct Neuroplasticity Mechanisms - Thais Ceresér Vilela; Alexandre Pastoris Muller; Adriani Paganini Damiani; Tamires Pavei Macan; Sabrina da Silva; Paula Bortoluzzi Canteiro; Alisson de Sena Casagrande; Giulia dos Santos Pedroso; Renata Tiscoski Nesi; Vanessa Moraes de Andrade; Ricardo Aurino de Pinho (Molecular Neurobiology, 2017)

Toxicity of TiO2 nanoparticles on the NRK52E renal cell line - Xavier Valentini; Lara Absil; Guy Laurent; Alexandre Robbe; Sophie Laurent; Robert Muller; Alexandre Legrand; Denis Nonclercq (Molecular & Cellular Toxicology, 2017)

Hyperpalatable Diet and Physical Exercise Modulate the Expression of the Glial Monocarboxylate Transporters MCT1 and 4 - Luis V. Portela; Andressa W. Brochier; Clarissa B. Haas; Afonso Kopczynski de Carvalho; Jussania A. Gnoato; Eduardo R. Zimmer; Eduardo Kalinine; Luc Pellerin; Alexandre P. Muller (Molecular Neurobiology, 2017)

An analysis of the sustainability index of micro- and small-sized furniture industries - Alexandre André Feil; Daniela Muller de Quevedo; Dusan Schreiber (Clean Technologies and Environmental Policy, 2017)

Insights into regional patterns of Amazonian forest structure, diversity, and dominance from three large terra-firme forest dynamics plots - Alvaro Duque; Helene C. Muller-Landau; Renato Valencia; Dairon Cardenas; Stuart Davies; Alexandre de Oliveira; Álvaro J. Pérez; Hugo Romero-Saltos; Alberto Vicentini (Biodiversity and Conservation, 2017)

Brain Insulin Administration Triggers Distinct Cognitive and Neurotrophic Responses in Young and Aged Rats - Clarissa B. Haas; Eduardo Kalinine; Eduardo R. Zimmer; Gisele Hansel; Andressa W. Brochier; Jean P. Oses; Luis V. Portela; Alexandre P. Muller (Molecular Neurobiology, 2016)

Anti-inflammatory Effect and Toxicology Analysis of Oral Delivery Quercetin Nanosized Emulsion in Rats - Gabriela Hädrich; Gustavo Richter Vaz; Michelle Maidana; Jadel Muller Kratz; Gecioni Loch-Neckel; Daniely Cornélio Favarin; Alexandre de Paula Rogerio; Flávio Manoel Rodrigues da Silva; Ana Luiza Muccillo-Baisch; Cristiana Lima Dora (Pharmaceutical Research, 2016)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Heritability for resistance to Puccinia psidii Winter rust in Eucalyptus grandis Hill ex Maiden in Southwestern Brazil - Aline Cristina Miranda; Mario Luiz Teixeira de Moraes; Evandro Vagner Tambarussi; Edson Luis Furtado; Edson Seizo Mori; Paulo Henrique Muller da Silva; Alexandre Magno Sebbenn (Tree Genetics & Genomes, 2013)

Western Style Diet Impairs Entrance of Blood-Borne Insulin-like Growth Factor-1 into the Brain - Marcelo O. Dietrich; Alexandre Muller; Marta Bolos; Eva Carro; Marcos L. Perry; Luis V. Portela; Diogo O. Souza; Ignacio Torres-Aleman (NeuroMolecular Medicine, 2007)